Predisposing Faktor yang Berhubungan dengan Penerimaan Program Vaksinasi Covid-19 pada Masyarakat - Yuni Lasmita; Misnaniarti Misnaniarti; Haerawati Idris (Jurnal Kesehatan Masyarakat Indonesia, 2021)
Background: Acceptance of the Covid-19 vaccine is a challenge in the success of the Covid-19 vaccination program. Objective: This study aims to achieve herd immunity and to analyze predisposing factors (age, gender, knowledge, and belief in the Covid-19 vaccine) in the community in the Alang Alang Lebar Community Health Center Work Area. Methods: This type of research is a quantitative study using a cross-sectional study. The population in this study is people who live in Talang Ke-lapa Village and Alang Alang Lebar Village aged 18-60 years, a sample of 211 people with the determination of the sample using the Proportionate Stratified Random Sampling technique, the data were analyzed univariately and bivariate. Results: The research conducted showed that there was a significant relationship between knowledge (p-value = 0.041) and trust in the Covid-19 vaccine (p-value = 0.000) and acceptance of the Covid-19 vaccination program. Meanwhile, the age variable (p=0.739) and the gender variable (p=0.838) had no relationship with the acceptance of the Covid-19 vaccination program. Conclusion: Efforts are needed to increase access to information related to Covid-19 vaccination so that people believe in the Covid-19 vaccine so that public acceptance of the Covid-19 vaccination program increases in the Alang Alang Lebar Health Center Work Area.